Green Consumption Awareness and Repurchase Intention on E-Commerce Platforms: The Mediating Role of Green Shipping Packaging - HANG NGA NGUYEN; Hien Nguyen Thi; Huyen Pham Thi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
Purpose. This study examines how Green Consumption Awareness influences Repurchase Intention on e-commerce platforms in Vietnam, focusing on the mediating role of Green Shipping Packaging. It aims to identify the behavioral mechanism through which consumers’ environmental awareness is converted into platform loyalty. Designs. A cross-sectional survey was administered to Vietnamese online shoppers; after data cleaning, 282 usable responses were analyzed. The study used exploratory factor analysis and confirmatory assessment, then applied partial least squares structural equation modeling (PLS-SEM) with bootstrapping (5,000 resamples) to test direct and indirect effects. Findings. Results show that Green Consumption Awareness is positively associated with Repurchase Intention, and Green Shipping Packaging partially mediates this relationship. Structural results further indicate that Subjective Norm strongly predicts demand for green packaging (β = .653, t = 11.34), while Perception shows a small negative effect on packaging demand (β = −.155, t = −3.12); Attitude was not significant. Demand for green packaging strongly predicts Repurchase Intention (β = .758, t = 32.75). Practical implications. E-commerce platforms and 3PLs should prioritize visible, credible green shipping solutions (e.g., recyclable/reusable parcel systems, transparent labeling) to convert consumer awareness into repeat purchases and support national Net Zero goals. Originality/value. This research isolates shipping packaging as a tangible mediating mechanism between environmental awareness and repurchase behavior in e-commerce—an underexplored nexus—providing actionable insights for firms and policy makers in emerging market Keywords: E-commerce, Green Consumption Awareness, Green Shipping Packaging, Repurchase Intention.